2022
DOI: 10.1177/15553434221103718
|View full text |Cite
|
Sign up to set email alerts
|

A Naturalistic Investigation of Trust, AI, and Intelligence Work

Abstract: Artificial Intelligence (AI) is often viewed as the means by which the intelligence community will cope with increasing amounts of data. There are challenges in adoption, however, as outputs of such systems may be difficult to trust, for a variety of factors. We conducted a naturalistic study using the Critical Incident Technique (CIT) to identify which factors were present in incidents where trust in an AI technology used in intelligence work (i.e., the collection, processing, analysis, and dissemination of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…A naturalistic approach was used to understand how intelligence professionals gained or lost trust in AI. We provide an overview of methods particularly relevant to this analysis; however, a more exhaustive description of the overall study can be found in Dorton & Harper (2022).…”
Section: Methodsmentioning
confidence: 99%
“…A naturalistic approach was used to understand how intelligence professionals gained or lost trust in AI. We provide an overview of methods particularly relevant to this analysis; however, a more exhaustive description of the overall study can be found in Dorton & Harper (2022).…”
Section: Methodsmentioning
confidence: 99%
“…The difficulty of modern technology development is evidenced by high rates of failed completion and transition (e.g., Dorton & Harper, 2022). To mitigate the difficulties and improve the likelihood of a successful transition, SD emphasizes decomposition of technologies into their mostbasic elements, clear and concise bite-sized requirements and specifications, quantitative and objective criteria, and minimal changes in design specifications across the development timeline; in other words, the removal and avoidance of complexity.…”
Section: Kelly Neville Resilience-focused Cognitive Engineeringmentioning
confidence: 99%
“…Developers of AI often conflate algorithmic performance with trustworthiness, ignoring the complexities of the sociotechnical system in which the AI will reside. There are dozens of factors affecting trust in AI, where explainability and predictability play prominent roles (Dorton & Harper, 2022). To that end, we have had considerable success in employing naturalistic CE methods to design intelligent systems to be both explainable and predictable.…”
Section: Steve Dorton Applying Naturalistic Research For the Developm...mentioning
confidence: 99%
“…We define successful transition as encompassing both a technology's integration into and positive contributions to a work system. Successful transition has been a challenge for decades (e.g., Dorton & Harper, 2022;Dwived, et al, 2015;Kheybari et al, 2020;Neville et al, 2008). Even when defined simply as completed technology that meets contractual requirements, the statistics are concerning.…”
Section: Introductionmentioning
confidence: 99%